Waterpipe smoking among health sciences university students in Iran: perceptions, practices and patterns of use - Ghafouri Nasim; Hirsch Jan D; Heydari Gholamreza; Morello Candis M; Kuo Grace M; Singh Renu F (BMC Research Notes, 2011)
Abstract Background In recent years waterpipe smoking has become a popular practice amongst young adults in eastern Mediterranean countries, including Iran. The aim of this study was to assess waterpipe smoking perceptions and practices among first-year health sciences university students in Iran and to identify factors associated with the initiation and maintenance of waterpipe use in this population. Results Out of 371 first-year health sciences students surveyed, 358 eight students completed a self-administered questionnaire in the classrooms describing their use and perceptions towards waterpipe smoking. Two hundred and ninety six responders met study inclusion criteria. Waterpipe smoking was common among first-year health sciences university students, with 51% of students indicating they were current waterpipe smokers. Women were smoking waterpipes almost as frequently as men (48% versus 52%, respectively). The majority of waterpipe smokers (75.5%) indicated that the fun and social aspect of waterpipe use was the main motivating factor for them to continue smoking. Of waterpipe smokers, 55.3% were occasional smokers, using waterpipes once a month or less, while 44.7% were frequent smokers, using waterpipes more than once a month. A large number of frequent waterpipe smokers perceived that waterpipe smoking was a healthier way to use tobacco (40.6%) while only 20.6% thought it was addictive. Compared to occasional smokers, significantly more frequent smokers reported waterpipe smoking was relaxing (62.5% vs. 26.2%, p = 0.002), energizing (48.5% vs. 11.4%, p = 0.001), a part of their culture (58.8% vs. 34.1%, p = 0.04), and the healthiest way to use tobacco (40.6% vs. 11.1%, p = 0.005). Conclusions Social and recreational use of waterpipes is widespread among first-year health sciences university students in Iran. Women and men were almost equally likely to be current waterpipe users. Public health initiatives to combat the increasing use of waterpipes among university students in Iran must consider the equal gender distribution and its perception by many waterpipe smokers as being a healthier and non-addictive way to use tobacco.